Chaucer's "Female Pantheon" in Troilus and Criseyde - McCulloch, Virginia Eleanor (My University, 1969)
This thesis examines the four prologues and the epilogue of the Troilus and Criseyde. Chaucer opens each prologue with the invocation of a pagan goddess and concludes the epilogue with an entreaty to the Christian Trinity and a tribute to Mary the mother of Jesus. This study examines classical and medieval mythology in treatises and in literature for the purpose of determining how it shapes and directs Chaucer's selection of a "female pantheon". The influence of mythology, both Christian and pagan, is shown as the formulating principle behind the basic philosophy, the religious tenets and the poetic imagery of the Troilus and Criseyde.
Keywords: English Language and Literature; English Language and Literature